Streptococcus pyogenes infection of tonsil explants is associated with a human β-defensin 1 response from control but not recurrent acute tonsillitis patients - Bell, S.; Howard, A.; Wilson, J.A.; Abbot, E.L.; Smith, W.D.; Townes, C.L.; Hirst, B.H.; Hall, J. (Molecular oral microbiology, 2012)
Summary Host defence peptides (HDP), including the defensins and hCAP‐18, function as part of the innate immune defences, protecting the host epithelia from microbial attachment and invasion. Recurrent acute tonsillitis (RAT), in which patients suffer repeated symptomatic tonsil infections, is linked to Streptococcus pyogenes, a group A streptococcus, and may reflect the impaired expression of such peptides. To address this, the defensin and hCAP‐18 messenger RNA expression profiles of 54 tonsils excised from control and RAT patients undergoing tonsillectomy were quantified and compared. Marked variation in expression was observed between individuals from the two groups, but statistically no significant differences were identified, suggesting that at the time of surgery the tonsil epithelial HDP barrier was not compromised in RAT subjects. Surgical removal of the tonsils occurs in a quiescent phase of disease, and so to assess the effects of an active bacterial infection, HaCaT cells an in vitro model of the tonsil epithelium, and explants of patient tonsils maintained in vitro were challenged with S. pyogenes. The HaCaT data supported the reduced expression of hCAP‐18/LL‐37, human β‐defensin 1 (HBD1;P < 0.01) and HBD2 (P < 0.05), consistent with decreased protection of the epithelial barrier. The tonsil explant data, although not as definitive, showed similar trends apart from HBD1 expression, which in the control tonsils but not the RAT patient tonsils was characterized by increased expression (P < 0.01). These data suggest that in vivo HBD1 may play a critical role in protecting the tonsil epithelia from S. pyogenes.